Peningkatan Kompetensi Profesionalitas Guru Madrasah Melalui Pendidikan dan Pelatihan ( Sebuah Analisis Terkait Materi Diklat) - Saidan, Saidan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
Research is an Analysis Related to Training Materials ". The background of this research is a question that always arises from stakeholders about the existence of education and training (Training) both in terms of Substantive Technical Subject Based Education (Mapel) and Non-Mapel in increasing the professionalism of madrasah teachers. The study used a qualitative descriptive approach with survey and interview methods. The formulation of the problem is "Can Substantive Technical Education for Subject Based Education or Non-Subject Education Can Improve Madrasah Teacher Professionalism?" The results showed that the Substantive Technical Training of subject teachers can only improve the professional competence of teachers related to the mastery of content or teaching material, structure, concepts and scientific thought patterns that support the subjects being taught. Whereas Non-Subject Substantive Technical Training can improve teacher competence in terms of professional and methodological development. To increase teacher professionalism that is intact both in the formulation of content, learning methodology and also competence in terms of ongoing professionalism and reflective action must go through both the Training which is subject based and non-subject.